Squamous Cell Bladder Cancer Associated with Large Bladder Stone: Literature Review and Its Case Report - Sawkar Vijay Pramod; Ferry Safriadi; Rizqia Abyaksa (Asian Pacific Journal of Cancer Care, 2022)
Bladder cancer is the most common urinary tract malignancy. Radical cystectomy is preferred as gold standard therapy for non-metastatic SCC, reflected from better survival rates than other treatment options such as partial cystectomy, chemotherapy, and radiation. Several factors are associated with the occurrence of bladder cancer, including bladder stone and infection ; such conditions suggestively could cause chronic irritation on the bladder surface epithelial, causing cancerous lesion to arise. Several literatures have showed positive outcome of patients with bladder cancer that underwent radical cystectomy. Thus, it is recommended to be performed on bladder cancer cases. Hereby we present a case of a 50-years old male who underwent radical cystectomy and bilateral ureterocutaneoustomy after previous trans urethral resection of bladder tumor (TURB-T) due to squamous cell bladder cancer. At the time of admission, he had bladder stone that based on imaging result, has already penetrated adjacent tissues. We also conducted literature review to assess our case with the other reports regarding the outcome of radical cystectomy for bladder SCC.